The Sacred Sites of Houston: A Novel Experiential Course for Undergraduate Medical Education on Religion and Spirituality - King, Nicholas (Journal of religion and health, 2021)
Medical schools are charged to deliver a curriculum on religion and spirituality (R/S), so a novel experiential course, the Sacred Sites of Houston, was developed. Sixty students completed the course consisting of 6 site visits. Post-course, participants described more general knowledge and knowledge of how each faith tradition describes medicine and health (p < 0.05 for all) except for Catholicism (p = 0.564 and p = 0.058). Ten course participants and 6 control non-course participants were interviewed following clinical rotations to assess the impact of the experiential course on R/S in the clinical setting. Themes from qualitative interviews such as R/S, barriers, interactions, and the course impact emerged. The importance of R/S in the patient-provider relationship and end-of-life care was prominent in course participant interviews compared to non-course participant control subjects. Participation in the course resulted in increased chaplain engagement and significant personal impact. These qualitative and quantitative findings indicate that an experiential course may be effective at addressing the deficit in R/S undergraduate medical education and help enhance the spiritually and religiously competent care of patients.